Exosome-based modulation of ferroptosis in neurological disorders: mechanisms, therapeutic potential, and translational challenges - Bao, Xiaoying; Chen, Liwei; Yu, Hong; Xie, Yunan; Luo, Liangxiao; Luo, Li; Wang, Hanbing; Chen, Rongbing; Cheng, Yongwei; Sun, Da; Zhang, Chunwu (Frontiers in Immunology, 2025)
Neurological disorders, including acute insults such as stroke and traumatic brain injury and chronic neurodegenerative diseases like Alzheimer’s disease and Parkinson’s disease, exert a profound global health burden. Ferroptosis, a distinct form of regulated cell death driven by iron accumulation, lipid peroxidation, and oxidative stress, has emerged as a central pathological mechanism across these conditions. Exosomes, nanoscale extracellular vesicles capable of crossing the blood-brain barrier and delivering functional cargos such as microRNAs, long non-coding RNAs, and proteins, have demonstrated remarkable potential in modulating ferroptotic signaling. Through regulation of the GPX4–GSH axis, ferritinophagy, iron homeostasis, and antioxidant pathways, exosome-based interventions offer neuroprotective benefits in diverse models of neurological injury. This review synthesizes current advances in the mechanistic understanding of ferroptosis and highlights emerging strategies leveraging exosomes as precision delivery platforms for ferroptosis-targeted therapy. We also discuss the translational challenges and future directions necessary to realize exosome-guided neuroprotection as a viable clinical paradigm.